Strengthening Strategies For Preventing Drug Abuse In Adolescents And Youth: A Holistic And Comprehensive Approach Based On Social Environment Interventions - Muhammad, Hidayat Adi (Jurnal Indonesia Sosial Sains, 2025)
The stagnation of the prevalence of drug abuse among adolescents and youth in Indonesia is a strategic issue that deserves serious attention, especially in the midst of the momentum of the demographic bonus towards a Golden Indonesia 2045. This phenomenon has the potential to have multidimensional impacts, ranging from a decrease in the quality of human resources, a decrease in productivity, to an inhibition of national competitiveness. The analysis shows that the main problem lies in the high risk behaviors among adolescents and youth—such as smoking, alcohol consumption, and nighttime activities—which are rooted in weak self-regulation skills due to a lack of social environmental support. This condition creates a recurrent vulnerability that maintains a stagnation in the prevalence of drug abuse in this age group. Meanwhile, policy support has been available through various instruments, such as the P4GN National Action Plan, Guidance and Counseling services in schools, Youth Care Health Services (PKPR), and the Generation Planning (GenRe) program. However, the effectiveness of the program is still limited because it has not touched the root of vulnerability thoroughly; Preventive interventions for adolescents and youth are fragmented and poorly coordinated, so the impact is not optimal. Therefore, this paper was prepared with the aim of formulating comprehensive and holistic prevention policy recommendations, based on a multi-level approach of social ecology, to significantly reduce the prevalence of drug abuse in adolescents and youth and build the foundation of sustainable prevention.